Volatility, asymmetric relationship, and hedging effectiveness : a study on derivative markets in Malaysia - Salami, Monsurat Ayojimi (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2018)
Return volatility severely affects equity portfolio or increases the cost in agricultural commodity as the major input for production. This triggers the need to re-examine the long-run relationship between underlying and futures markets and also the effectiveness of the offsetting position in futures markets. With theoretical and empirical evidence, understanding the return volatility, the long-run relationship between underlying and futures prices and the hedging effectiveness are the three main objectives of this study. It is hoped that this study will assist policymakers on how to intervene in markets with the right policies. This is because interconnection between underlying and futures prices as well as hedging the underlying position in the futures market are empirically emphasized. Addressing volatility problems with the wrong policy may affect the economy negatively. Also, it has been documented that the futures market plays an important role in managing price risk exposure, thus determining the optimality of hedge ratio is crucial to avoid hedging errors that might result in over hedging or under hedging. For the purpose of this study, 16 hypotheses have been developed based on related literature. Also, the influence of structural break and the effects of the GST announcement are examined. The findings of this study are explained based on the Efficiency Market Hypothesis (EMH), Arbitrage Pricing Theory (APT) and Law of One Price (LOP). The period of study ranges from June 2009 to November 2016. This study uses daily closing prices of the Crude Palm Oil (CPO), Kuala Lumpur Composite Index (KLCI), CPO Futures (CPO-F), KLCI Futures (KLCI-F) and Basis. It has been documented in previous studies that basis is an important variable with predictive power to forecast changes in underlying prices and useful in improving hedging ratio. To achieve the three objectives, this study employs Generalized Autoregressive Conditional Heteroscedasticity (GARCH), Threshold Generalized Autoregressive Conditional Heteroscedasticity (TGARCH) and Multivariate-GARCH (M-GARCH), to specifically examine the return volatility of the Malaysian underlying markets (CPO and KLCI), the Johansen cointegration test and Vector Error Correction Model (VECM) for symmetric relationship, and the Threshold Autoregressive (TAR) together with the Momentum Threshold Autoregressive (M-TAR) for the asymmetric relationship between CPO and CPO-F, KLCI and KLCI-F, and CPO and KLCI. This study uses the M-GARCH model to quantify the optimal hedge ratio and hedging effectiveness. This study establishes that return volatility is persistent and clustered in the Malaysian derivatives market while asymmetric impact of shocks for TGARCH estimation is statistically insignificant. The M-GARCH model establishes that there exists a volatility spillover between CPO and KLCI market. This study also finds an asymmetric relationship between underlying and futures markets in the pre-GST announcement. The result of hedging effectiveness shows that hedging in the Malaysian derivatives market is effective, both in the CPO-F and KLCI-F, while the optimal hedge ratio of each market is significantly different. The optimal hedge ratio required from the Malaysian stock index is higher than the Malaysian commodity market. This study confirms that basis is an important variable for modelling return volatility, asymmetric relationship and quantifying hedging effectiveness. Proper monitoring and appropriate policy intervention will enhance contribution of Malaysian derivatives markets on economic performance by increasing global mobility of funds to the country. This study significantly contributes new knowledge to the literature especially in the field of derivatives studies.